Exploring the Relationship between Fossil Fuel Energy Consumption, Renewable Energy Consumption and Human Capital Index: A Study From Thailand - Purwanto, S. K.; Sinaga, Obsatar (International Journal of Energy Economics and Policy, 2021)
This study examines the trend in human capital index (HCI) in the economy of Thailand during 1990-2010 while considering the fossil fuel and renewable energy consumption as main independent variables. However, some macroeconomic variables like expenditure side real GDP, output side real GDP, population, number of persons engaged/ employed, are average annual hour of working are added as controls. Overall three empirical findings are provided considering the separate and combine effect of fossil fuel, energy consumption from renewable sources on HCI along with control variables. Findings show that fossil fuel is negatively while renewable energy is positively impacting on human capital index in Thailand over last two decade. Study findings have provided some sensible and rationale contributions in the literature of environmental sustainability and community as well. However, limitations are also attached to this study. First, time duration of the study has only observed the horizon until 2010 while ignoring the recent decade. Second, human capital index is only observed through educational measure. Third, time series trend like short run and long run are neglected. Fourth, carbon emission in the natural environment was also not included in the model, yet it might be a significant determinant of HCI. Besides, practical implication of the study justify for the support of various stakeholders. Keywords: Human capital index, renewable energy consumption, fossil fuel consumption, Thailand. JEL Classifications: K32, E24. DOI: https://doi.org/10.32479/ijeep.10910